African Futures: Thinking about the future in word and image - Heidenreich-Seleme ,Lien; O'Toole ,Sean (Germany Kerber Verlag, 2016)
How do artists and scholars imagine Africa's futures? What forms and narratives have African artists developed to address these futures? Who generates knowledge about Africa? And ,what are the different languages we use to speak about Africa's political ,technological and cultural tomorrows? This book gathers the creative speculations of leading Afrcan and diasporic artists , writers and thinkers.
How do artists and scholars imagine Africa's futures ? What forms and narratives have African artists developed to address these futures? Who generates knowledge about Africa? And ,what are the different languages we use to speak about Africa's political ,technological and cultural tomorrows? This book gathers the creative speculations of leading Afrcan and diasporic artists , writers and thinkers.